PENERAPAN PROFILE MATCHING UNTUK PENILAIAN PEKERJA KONTRAK DI PT. ABC - Rizal Rachman; Nanang Hunaifi; Ali Mulyawan (STMIK Mardira Indonesia, Bandung, 2020)
The best contract workers are contract workers who display certain values and criteria determined by the company. Contract Workers who have the criteria to meet the specified conditions will receive an award as the best Contract Workers in the company where the Contract Workers work, as implemented by PT. ABC. There are several evaluation criteria in determining the best contract workers in this company, namely: Productivity (Quality), Quality Internal Control (Quality), Teamwork (Cooperation), Initiative (Initiative) and Absence (Attendance). So that in writing this thesis conducted research that is intended to produce and can assist in the selection of the best contract workers. The aim is to test the Profile Matching method in determining the best Contract Worker, to find out how the process has gone in determining the best Contract Worker and who is the best Contract Worker at PT. ABC. This was obtained from the results of the calculation and comparison of the profiles of the best Contract Workers who emphasized productivity and quality. With a situation where the number of the best contract worker candidates is more than the best contract worker position, a ranking of the best contract worker candidates will be ranked so that later the highest competency weighting will be obtained to fill the best contract worker.Keywords: Application, Profile Matching, Contract Workers DOI : http://doi.org/10.5281/zenodo.4320256